ART 900 radio base station monitoring system / Azmi Hashim, Mohd Ariff Abdullah and Mohd. Pauzi Mohd . Yusoh - Hashim, Azmi; Abdullah, Mohd Ariff; Mohd . Yusoh, Mohd. Pauzi (1992)
The objective of this project report is to give an overview for the ART 900 Radio Base Station (RBS) monitoring system which is similiar to SCADA (Supervisiory Control And Data Acquisition) system.